Getty vocabularies - Getty Research Institute (2020)
[Engl.:] The Getty Vocabularies contain structured terminology for art, architecture, decorative arts, archival materials, visual surrogates, conservation, and bibliographic materials. Compliant with international standards, they provide authoritative information for catalogers, researchers, and data providers.